Inventarisasi Bryophyta, Pteridophyta, Gymnospermae Di Kabupaten Lamongan - Dwi Zulianti; M. Ainul Mahbubillah; Nynda Ayu Nadira Savitri; Rofiatun Solekha (Program Studi Pendidikan Biologi, 2021)
Indonesia has rich of plant species because of its habitat variation. Bryophyta, Pteridophyta, and Gymnospermae mostly grow on highland habitat. Height of the habitat causes change of micro-climate, especially humidity. Lamongan District of East Java Indonesia Jawa Timur is a lowland area so that difficult to find species of those three taxa. For educational purposes, data collection of the 3 taxa species that grow in Lamongan District is needed. The research was carried out by identifying plants Bryophyta, Pteridophyta, and in Lamongan District. The results of the study found that there were 3 Bryophyte species: Marchantia polymorpha, Polytrichum sp, and Riccia sp.; 3 Pteridophyte species: Pteridium aquilinum, Adiantum philippens, and Telmatoblechnum indicum; and 2 Gymnosperm species: Cycas rumphii, and Gnetum gnemon.